Leptin, but not ghrelin, is associated with food addiction scores in a population-based subject sample - Wittekind, Dirk Alexander; Kratzsch, Jürgen; Mergl, Roland; Baber, Ronny; Wirkner, Kerstin; Schroeter, Matthias L.; Witte, A. Veronica; Villringer, Arno; Kluge, Michael (Frontiers in Psychiatry, 2023)
Ghrelin and leptin are both peptide hormones and act as opposing players in the regulation of hunger, satiety and energy expenditure. Leptin reduces appetite and feelings of hunger and is secreted mainly by adipocytes, while ghrelin increases appetite and food intake and reduces metabolic rate. Both hormones have been implicated in addictive disorders. Ghrelin was shown to have pro-addictive effects while leptin's role in addiction yields more conflicting results. Their involvement in the regulation of both food intake and addictive behaviors make them interesting candidates when investigating the regulation of food addiction. However, only few human studies have been performed and large-scale studies are lacking to date. We aimed to investigate the association between total ghrelin and leptin serum levels with scores in the Yale Food Addiction Scale (YFAS). Subjects were recruited in the LIFE Adult cohort. 909 subjects were included in the analysis and we performed univariate multiple linear regression models, adjusted for age, sex (in total group analyses only), alcohol consumption, smoking status, BMI scores, cortisol concentrations, Center for Epidemiological Studies Depression Scale (CES-D) and the 7-item Generalized Anxiety Disorder Scale (GAD-7) sum scores. The dependent variable was the YFAS score. In men, leptin serum levels showed a significant positive association (standardized ß=0.146; p=0.012) with the YFAS score. This finding was confirmed in an extreme-group comparison: men in the highest quartile of leptin levels had significantly higher YFAS sum scores than men in the lowest quartile (1.55 vs. 1.18; p=0.00014). There was no association with YFAS sum score in the total group (standardized ß=-0.002; p=0.974) or in women (standardized ß=-0.034; p=0.674). Total serum ghrelin showed no association with YFAS sum score neither in the total group (standardized ß=-0.043; p=0.196) nor in men (n=530; standardized ß=-0.063; p=0.135) or women (n=379; standardized ß=-0.035; p=0.494).Our findings are in line with previous literature and suggest that total ghrelin serum levels are not associated with food addiction scores. Leptin had been previously shown to be associated with food addiction and we confirmed this finding for men in a large, population-based approach.